Phase Transitions: Explicit Dynamics of Diffuse Interface in Phase‐Field Model (Adv. Theory Simul. 1/2021). Issue 1 (14th January 2021) - Yang, Chao; Huang, Houbing; Liu, Wenbo; Wang, Junsheng; Wang, Jing; Jafri, Hasnain Mehdi; Liu, Yu; Han, Guomin; Song, Haifeng; Chen, Long‐Qing
Abstract : As the physical boundary of different phases/grains/domains at the mesoscopic scale, interfaces play an important role during phase transition and interfacial chemical reactions. The theoretical derivations presented by Houbing Huang and co‐workers in article number 2000162 not only present the relationship between the diffuse interfacial velocity and the effect of driving force and interfacial curvature, but also clarify the equivalent method between the phase‐field dynamics and the sharp‐interfacial dynamics, which reveals the physical meaning of the diffuse interfacial dynamical equation from a different perspective.